Peran Bank Wakaf Mikro Dalam Penguatan Modal dan Pemberdayaan Usaha Mikro di Surabaya - Muhammad Faiq Ramadhan; Raditya Sukmana (Universitas Airlangga, 2019)
This study aims to determine whether there are differences in the benefits obtained by micro-entrepreneurs between before obtaining financing capital from a Bank Wakaf Mikro and after obtaining financing capital from a Micro Waqf Bank. The approach used is a quantitative approach using analytical techniques t-paired test and using SPSS 20. The data used is primary data from questionnaires distributed to customers of Bank Wakaf Mikro. The results of this study indicate that the provision of capital carried out by Bank Wakaf Mikro has been effective in increasing the profits of the business of Bank Wakaf Mikro customers so that the welfare of the customers also increases thanks to the financial assistance provided. In addition, the role of guidance provided by the Bank Wakaf Mikro also plays a role in improving customer performance in carrying out its business.Keywords: Bank Wakaf Mikro, Business Capital, Micro Business, Empowerment, Profit